Functionalization Using Biocompatible Carboxylated Cyclodextrins of Iron-Based Nanomil-100 - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Canon-Mancisidor, W; Canon-Mancisidor, W (Elsevier Ltd, 2021)
Here we report the first example of nanoMIL-100 particles modified with monomeric cyclodextrin derivatives of different length by exploiting strong interactions between non-saturated iron trimers at the external surface and carboxylate functionalities located at the end of biocompatible and flexible linkers of cyclodextrins. The main results revealed that, after the functionalization, the cyclodextrins are selectively located at the external surfaces covering the nanoparticles. Z potential measurements show that this functionalization induced changes respect to the bare nanoMIL-100 particles, however, the presence of the cyclodextrins does not modify the size neither porosity of the nanoparticles. The amount of cyclodextrins attached, investigated by thermogravimetry, increases with the length of the linker between CD cavity and nanoparticle surface, reaching up a 9 % wt. Auger spectroscopy suggested a clear predominant sp3 character after the functionalizations (vs. sp2 predominance in the unmodified nanoMIL-100). This study supposes the creation of an alternative family of hybrids based on carboxylated monomeric cyclodextrins. © 2021 Elsevier Ltd